Middle power identities of Australia and South Korea: comparing the Kevin Rudd/Julia Gillard and Lee Myung-bak administrations. Issue 2 (4th March 2018) - Teo, Sarah
ABSTRACT: This paper explores the middle power identities of Australia and South Korea during the Kevin Rudd/Julia Gillard (2007–2013) and Lee Myung-bak (2008–2013) administrations. Considering the problems in the existing position, behaviour, impact and identity-based definitions of middle powers, examining how self-identified middle powers have constructed such an identity would offer useful insights into the middle power concept. Relying on a framework that captures an identity's content and contestation, this paper argues that while Australia and South Korea have assumed a middle power identity, their visualisations of this identity are slightly different. Australia has understood its middle power identity in both economic and security terms, whereas South Korea appears to have connected such an identity more with the economic dimension. These differences affect how they envision their respective middle power roles in international affairs.